Preparation of neodymium hydroxide nanorods and neodymium oxide nanorods by a hydrothermal method - N. Ekthammathat (2018)
© 2015, Inst Materials Physics. All rights reserved. One dimensional Nd(OH) < inf > 3 < /inf > nanorods were successfully prepared through a 180 oC and 20 h hydrothermal reaction. Subsequently, the Nd(OH) < inf > 3 < /inf > nanorods were calcined at 450–600 oC for 2 h. Their phases and morphologies were characterized by XRD, SEM and TEM. The XRD patterns revealed the hexagonal Nd(OH)3 phase of the precursor and the hexagonal Nd < inf > 2 < /inf > O < inf > 3 < /inf > phase of the final product. Upon calcination at 550 °C and above for 2 h, the hexagonal Nd(OH)3 nanorods were transformed into the hexagonal Nd < inf > 2 < /inf > O < inf > 3 < /inf > nanorods with the shape remained unchanged. In this research, uniform Nd(OH) < inf > 3 < /inf > nanorods and Nd < inf > 2 < /inf > O < inf > 3 < /inf > nanorods with the increase in size by the high temperature calcination were detected.